2001
DOI: 10.1161/01.cir.104.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Study for Immunosuppressive Treatment of Inflammatory Dilated Cardiomyopathy

Abstract: These data demonstrate a long-term benefit of immunosuppressive therapy in patients with dilated cardiomyopathy and HLA upregulation on biopsy specimens. Thus, restoration of immunosuppressive therapy for such patients should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
274
2
31

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(321 citation statements)
references
References 27 publications
11
274
2
31
Order By: Relevance
“…Kühl et al (9) also demonstrated that immunosuppressive treatment in a subgroup of patients with dilated cardiomyopathy having continuing active inflammatory process results in a clinical, hemodynamic, and immunohistological improvement in 60%-70% of patients. Moreover, Wojnicz et al (10) showed a long-term benefit of immunosuppression with prednisone and azathioprine in patients with dilated cardiomyopathy because of immunohistologically proven myocarditis. However, we had no proven data regarding the status of inflammatory process in the myocardium of our patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Kühl et al (9) also demonstrated that immunosuppressive treatment in a subgroup of patients with dilated cardiomyopathy having continuing active inflammatory process results in a clinical, hemodynamic, and immunohistological improvement in 60%-70% of patients. Moreover, Wojnicz et al (10) showed a long-term benefit of immunosuppression with prednisone and azathioprine in patients with dilated cardiomyopathy because of immunohistologically proven myocarditis. However, we had no proven data regarding the status of inflammatory process in the myocardium of our patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…The first and third patients, in accordance with the EMB results, were treated with immunosuppressive combination therapy. In addition to the studies published by Midei 18 and Melvin 19 of PPCM patients, the effectiveness of such therapy was demonstrated in patients with "nonpregnancy-associated myocarditis" in two randomized trials by Wojnicz 20 and Frustaci 21 . In both of our patients treated with immunosuppressive therapy, the number of infiltrating inflammatory cells significantly decreased, but the effect on the improvement of LV function was not entirely convincing.…”
Section: Discussionmentioning
confidence: 99%
“…Its effect has been studied with promising results in animal models and also in a pilot proof-of-concept study of 20 women 23 . The use of immunosuppressive therapy is offered as a parallel to studies with inflammatory cardiomyopathy in patients with biopsy-proven myocarditis, where a viral (or other) genome is not present in the myocardium 20,21 . There are only limited data from patients with PPCM.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of DCM are multifactorial, but a viral or immune mechanism is suspected in some cases (2) because examination of heart tissues obtained during surgery has revealed inflammatory lesions in many patients with DCM (3). On the basis of these findings, several immunosuppressive therapies, including steroid and azathioprine administration (4,5), immunoadsorption (6), and Ig therapy (2), have been attempted. Although the general outcome of these treatments was disappointing, immunoadsorption therapy increased the survival rate for a subset of patients by 5 years after treatment (7).…”
Section: Ilated Cardiomyopathy (Dcm)mentioning
confidence: 99%